Predicting customer lifetime value for hypermarket private label products - Lin, Hsin-Hui; Li, Hsien-Ta; Wang, Yi-Shun; Tseng, Timmy H.; Kao, Ya-Ling; Wu, Min-Yi (Journal of Business Economics and Management, 2017)
This study develops a model to predict customer lifetime value for hypermarket private label products. It examines the relationships among store awareness, store image variables (i.e., service quality, price/value, convenience, and product quality), private label image, repurchase intention, and customer lifetime value and investigates the moderating role of image fit. The originality of this study lies in filling the gap of previous research on antecedents of private label customers’ behavior by considering store awareness, image fit, and customer lifetime value. Partial least squares structural equation modeling was used to analyze data. The results indicate the following. Store image variables (except product quality) and store awareness affect repurchase intention directly or indirectly through private label image. Image fit moderates the relationships between store image variables (except product quality) and private label image. Private label image facilitates customer lifetime value. This study provides several theoretical and practical implications for hypermarket private label product developments.